BENEFICIARY OF RESOLUTION BANK BY INDONESIA DEPOSIT INSURANCE CORPORATION - Napitupulu, Diana RW (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2022)
As an intermediary institution that functions to mobilise public funds, the bank has the potential to experience failure or fraud, which can cause ad decline in the bank's soundness (through CAMEL; Capital, Assets, Management, Earnings, and Liquidity). The Deposit Insurance Corporation was formed to guarantee limited deposit funds (limited guarantee) as a substitute for a blanket guarantee. LPS also has an active role in maintaining the stability of the banking system by its authority where after the OJK declares a failed bank, the banks are handed over to LPS, for non-systemic failed banks, a settlement is carried out by a rescue (at the expense of the shareholders) and not perform a rescue (liquidate the failed bank). If the bank failed to have a systemic impact, the IDIC (LPS) would take care of the Systemic Failed Bank, placing a temporary capital placement (PMS) to make it sound and resale it within 3 years. The issue is: How does failing bank restructuring meets the principle of benefit by the Indonesia Deposit Insurance Corporation? The type of this research is juridical-normative research and legal materials traceability technique using qualitative analytical. This research approach uses the statute approach, conceptual approach, and historical approach. The conclusion of this paper is Resolution Bank or restructuring of the failed bank by LPS that meets the beneficiary principle must carry out the following the four (4) categories of Commercial Banks based on Business Activities (BUKU),Â where for categories 3 and 4, a long period of restructuring is required because the bank has many derivative products.